Climate Variability in the Sudano-Guinean Transition Area and Its Impact on Vegetation: The Case of the Lamto Region in Côte D'Ivoire. (13th February 2014) - Diawara, A.; Yoroba, F.; Kouadio, K. Y.; Kouassi, K. B.; Assamoi, E. M.; Diedhiou, A.; Assamoi, P.
Abstract : Based on unique 50-year datasets from 1962 to 2011, this study diagnoses the variability of climate at Lamto (6.13°N, 5.02°W) in Côte d'Ivoire. A combined pluviothermal index is used to identify climate regions of West Africa. The interdecadal change of the climate is analyzed along with a discussion on the West African Monsoon (WAM) circulation. The impact of vegetation is also analyzed. It is shown that Lamto has mainly a subhumid climate but, in some particular years, this area has a humid climate. Two decades (1962–1971 and 2002–2011) exhibit rainfall excess and the last three ones (1972–1981, 1982–1991, and 1992–2001) show a rainfall deficit that affected West Africa in the early 1970s. The meridional wind field from 1000 hPa to 700 hPa is used to study the WAM variability. The level of the WAM is the lowest ( ~ 860–890 hPa) during the active period of the northern wind coming from the Sahara desert (November–February). During 1962–1971 and 2007–2009, the depth of the monsoon at Lamto reaches 300 hPa with an increase in the rainfall. A relationship between potential evapotranspiration and the climate highlights rainfall deficit in 1969 and rainfall excess in 2001–2011.